Enterprises Resource Planning (Erp) Implementation Factors: A Comparative Study: India and China - C.A, Aboobakkar Siddeeque (2008)
In today’s dynamic business world, efficiency is considered to be one of the most important factors to gain competitive advantage. As every business face contention they should not only challenge to produce a better and more reliable product but also should provide a better customer focused delivery mechanism. In the mean time, they are enforced to minimize their production costs as well as their overhead costs and bring efficiency in all their operations. These can be achieved through developing a superior information system which is through a highly reliable infrastructure and a more efficient management system. ERP Systems are born to bring efficiencies in the bottleneck of business’s information system and to provide an integrated system which capable to handle far more complex transactions and yet providing a highly dependable system. Enterprise Resource Planning (ERP) systems are incorporated; enterprise-wide systems that offer automated support for standard business processes within organizations and improve their business processes. It has been effectively applied by number of firms throughout world especially in developed countries. However, in recent years there has been a growing increase in the usage of ERP systems in developing countries such as India and China. These ERP systems are the most integrated information systems that cut across a variety of organizations and functional areas in Indian and Chinese organisation. It has been experienced that the majority of ERP systems proved to be a failure either in the design or its implementation. A number of reasons contribute in the success or failure of ERP systems. The main purpose of this research is to examine and establish the factors that facilitate or inhibit the success of ERP implementation in India and China and recognize what are the hardships and complications in implementing ERP in Indian and Chinese business atmosphere. A brief research has been conducted to compare the implementation practices of ERP in India vs. China. This research is preceded with combined methods of qualitative and quantitative data. Most of the Primary data are mainly collected through questionnaire surveys via e-mail, interviews, face-to3 face and telephone. Secondary data are collected from second-hand sources, such as websites, journals, books, etc. In this paper, ten (10) commonly accepted Critical Success Factors (CSFs) are identified based on the relevant literature. With better understanding of the comprehensive identification of CSFs and criticality ranking each factor, the respondents were asked to answer important degree of ERP critical success factors in their firms using a Likert-scale ranging from 1 to 10 (1: most important, 10: least important). The main aspects were top management support, Project management, Business process reengineering, Change management, Business plan and vision, training and education, Effective communication, Users involvement, Culture factors, Consultant and vendor support. I believe that the understanding of these factors will expand the perception of ERP implementations and will help evade implementation mistakes, thereby improving the rate of success in both countries.